Research on air-water coordinated operation of water side free cooling system based on improved particle swarm optimization algorithm - Ma Keyan; Lv Jie; Zhang Jili (E3S Web of Conferences, 2022)
Water side free cooling is an important technology for cooling water system to use natural cooling source for energy saving, especially in the field of data center and industrial production. However, the operation regulation of water side free cooling system was lack of scientific basis. This process involves the two-phase circulation of air and cooling water, which requires the coordinated operation of air and water to further optimize the energy consumption. The coordinated operation of air and water includes the coordination of air and water flow in each cooling tower and the matching of the operating numbers of equipment in the system. Firstly, based on the characteristics of the cooling tower, the key equipment in the water side free cooling system, the air-water two-phase heat transfer model in the cooling tower was established. Then, according to the heat transfer model and power model of each equipment in the system, the optimization objectives and constraints are established. An improved particle swarm optimization (PSO) algorithm was proposed to solve the problem of wind water collaborative optimization of water side free cooling system. Finally, this paper takes a small data center cooling water system as an example to analyze the optimization performance of the improved particle swarm optimization algorithm. The simulation results showed that the excellent rate obtained by the improved algorithm can be increased by 36.9%, which is more energy-saving. This method can provide a reference for the energy-saving optimization of water side free cooling system.